Precipitating Factors of Acne Vulgaris at Dr. Saiful Anwar Hospital Malang - Sinta Murlistyarini; Alfonsus Rendy Laksditalia Nugroho; Diane Tantia Sari; Silfia Mandasari (Jurnal Berkala Epidemiologi, 2021)
Background: Acne vulgaris (AV) is an inflammatory disease of the pilosebaceous unit, which often causes stress and disrupts quality of life. Correctly identifying precipitating factors and preventing disease development will holistically increase the effectiveness of acne therapy, enabling better therapeutic outcomes to be achieved. Purpose: The objective of this study is to identify the clinical profile and precipitating factors of AV patients who visited Dr. Saiful Anwar Hospital between 2015 until 2017. Methods: This was a descriptive study, using a retrospective case study approach. The sample data was collected from medical records of AV patients from the period of 2015–2017 who met the following inclusion criteria: new AV cases with a complete medical record including gender, age, and precipitating factors. The dependent variable of this study was new AV patients, while the independent variables were the patient clinical profile and precipitating factors. Results: This study included 930 samples, with the number of female patients significantly higher (75.48%) than the number of males. The highest AV prevalence was found in the 15–24 years age group. The most common precipitating factors in females were hormonal issues, stress, and cosmetics; in males, these were stress, genetics, and dietary factors. Conclusion: The incidence of AV at Dr. Saiful Anwar Hospital mostly occurs in the 15–24 years age group, with varying trigger factors. The most frequent AV trigger factor in female patients was hormonal issues; in males, this was stress.